Association of food industry ties with findings of studies examining the effect of dairy food intake on cardiovascular disease and mortality: systematic review and meta-analysis. Issue 12 (4th December 2020) - Chartres, Nicholas; Fabbri, Alice; McDonald, Sally; Diong, Joanna; McKenzie, Joanne E; Bero, Lisa
Abstract : Objective: To determine if the association of dairy foods with cardiovascular disease (CVD) outcomes differs between studies with food industry ties versus those without industry ties. To determine whether studies with or without industry ties differ in their risk of bias. Eligibility criteria: We included cohort and case–control studies that estimated the association of dairy foods with CVD outcomes in healthy adults. Information sources: We searched eight databases on 1 February 2019 from 2000 to 2019 and hand searched reference lists. Risk of bias: We used the Risk of Bias in Non-Randomised Studies-of Exposure tool. Included studies: 43 studies (3 case–controls, 40 cohorts). Synthesis of results: There was no clear evidence of an association between studies with industry ties (1/14) versus no industry ties (8/29) and the reporting of favourable results, risk ratio (RR)=0.26 (95% CI 0.04 to 1.87; n=43 studies) and studies with industry ties (4/14) versus no industry ties (11/29) and favourable conclusions, RR=0.75 (95% CI 0.29 to 1.95; n=43). Studies with industry sponsorship, (HR=0.78; n=3 studies) showed a decreased magnitude of risk of CVD outcomes compared with studies with no industry sponsorship (HR=0.97; n=18) (ratio of HRs 0.80 (95% CI 0.66 to 0.97); p=0.03). Strengths and limitations of evidence: Every study had an overall high risk of bias rating; this was primarily due to confounding. Interpretation: There was no clear evidence of an association between studies with food industry ties and the reporting of favourable results and conclusions compared with studies without industry ties. The statistically significant difference in the magnitude of effects identified in industry-sponsored studies compared with non-industry-sponsored studies, however, is important in quantifying industry influence on studies included in dietary guidelines. PROSPERO registration number: CRD42019129659.